Distribution and sources of particulate mercury and other trace elements in PM2.5 and PM10 atop Mount Tai, China. (1st June 2018) - Qie, Guanghao; Wang, Yan; Wu, Chen; Mao, Huiting; Zhang, Ping; Li, Tao; Li, Yaxin; Talbot, Robert; Hou, Chenxiao; Yue, Taixing
Abstract: The concentrations of particulate mercury (PHg) and other trace elements in PM2.5 and PM10 in the atmosphere were measured at the summit of Mount Tai during the time period of 15 June – 11 August 2015. The average PHg concentrations were 83.33 ± 119.1 pg/m 3 for PM2.5 and 174.92 ± 210.5 pg/m 3 for PM10 . Average concentrations for other trace elements, including Al, Ca, Fe, K, Mg, Na, Pb, As, Se, Cu, Cd, Cr, V, Mo, Co, Ag, Ba, Mn, Zn and Ni ranged from 0.06 ng/m 3 (Ag) to 354.33 ng/m 3 (Ca) in PM2.5 and 0.11 ng/m 3 (Co) to 592.66 ng/m 3 (Ca) in PM10 . The average concentrations of PHg were higher than those at other domestic mountain sites and cities in other counties, lower than those at domestic city sites. Other trace elements showed concentrations lower than those at the domestic mountain sites. Due possibly to increased control of emissions and the proportion of new energy, the PHg and trace element concentrations decreased, but the PHg showed concentrations higher than those at the Mountain sites, this showed that the reasons was not only severely affected by anthropogenic emissions, but also associated with other sources. The concentration changed trend of the main trace elements indicated that PHg, trace elements and particle matters present positive correlation and fine particulate matter has a greater surface area which was conductive to adsorption of Hg and trace elements to particles. On June 19, June 27 and July 6, according to the peak of mercury and trace elements, we can predict the potential sources of these three days. The results of principal component analysis (PCA) suggested that, crustal dust, coal combustion, and vehicle emissions were the main emission sources of PHg and other trace elements in Mount Tai. The 24-h backward trajectories and potential source contribution function (PSCF) analysis revealed that air masses arriving at Mount Tai were mainly affected by Shandong province. Mount Tai was subjected to five main airflow trajectories. Clusters 1, 2, 3, and 5 represented four pathways for local and regional sources and cluster 4 originated long-distance transportation. Central Shandong was the main source regions of PHg, Pb, Se, As, Cu and Cd. Southeastern and northwestern Shandong province and northern Jiangsu province were the most polluted source regions of Mn, Zn, and Ni. The crustal elements Fe and Ca had similar distributions of potential source regions, suggested by the highest PSCF values in southeastern Shandong and northern Jiangsu. Highlights: PHg characteristic was first determined in the high coal-fired area near Mount Tai. The distributions of elements in PM2.5 and PM10 at high altitude were compared. The transport pathways and potential source regions of risk elements were analyzed.